Pengaruh Level Premix dalam Pakan Komplit Berbasis Limbah Isi Rumen Terfermentasi Terhadap Status Fisiologis Sapi Bali - Dopong, Trifena; Abdullah, M. S; Marawali, Aloysius (Yayasan Sumber Daya Manusia Cerdas, 2025)
The purpose of the study was to determine the effect of premix level in complete feed based on fermented rumen content waste on the physiological status of Balinese cattle. The livestock used is 4 Balinese cows, aged 1-1.5 years with a weight range of 69 kg - 74 kg. The experimental method used was the Latin Square Design (RBSL) with 4 treatments and 4 periods as a repeat. The treatment in this study: P0: complete feed without premix (control); P1: complete feed +0.50% premix; P2: complete feed +1% premix ; P3: complete feed +1.5% premix. The data obtained was analyzed using analysis (ANOVA). Based on the results of the study, the average rectal temperature P0: 153.71±38.420C, P1: 153.80±38.450C, P2: 153.49±38.370C, P3: 153.32±38.330C, heart rate times/minute P0: 331.00±82.75; P1: 331.00±82.75; P2: 327.00±81.75; P3: 328.00±82.4, and respiratory rate per second±minute, P0: 84.0021.00; P1: 81.00±20.25; P2: 83.00±20.75; P3: 82.00±20.5. The results of the analysis Statistics showed that the treatment had no real effect (P>0.05) on rectal temperature, heart rate and respiratory rate of Balinese cows. It was concluded that the application of premix levels of up to 1.5% in complete feed containing fermented rumen content waste did not have a negative impact on the physiological status of Balinese cattle because it was in the normal range.